The Implementation of Chatgpt as Pedagogical Tool for Vocabulary Learning at Tenth Grade Students of Ma Miftahul Ulum Bettet Pamekasan - Ulfah; Rini Listyowati; Rohaniyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to investigate the implementation of ChatGPT as a pedagogical tool in English vocabulary learning and to explore students' learning experiences in its use. This study used a qualitative approach with a case study design conducted in grades X-I at MA Miftahul Ulum Bettet Pamekasan. Participants consisted of 41 students, with 20 students selected for interviews using simple random sampling. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using qualitative descriptive analysis. The findings indicate that ChatGPT implementation was carried out systematically through three main stages: pre-activity, during-activity, and post-activity. During the during-activity stage, ChatGPT was actively used for vocabulary practice, prompt creation, and interactive quizzes, which encouraged student-centered and collaborative learning. Furthermore, the results indicate that students' learning experiences can be categorized into cognitive, positive, and effective aspects. Cognitively, ChatGPT facilitated better vocabulary comprehension and retention through repetition and contextual learning. Positively, students showed positive attitudes, increased motivation, and higher engagement due to the interactive and enjoyable learning experience. ChatGPT effectively improves learning efficiency by providing immediate feedback and easy access to information. Overall, this study highlights that ChatGPT is not only a technological tool but also an effective pedagogical instrument that improves vocabulary acquisition and student engagement. These findings suggest that integrating AI-based tools into language learning can significantly improve instruction quality and support a more interactive and meaningful learning environment.